Perbandingan Biaya dan Waktu Erection PCI Girder dengan Crawler Crane dan Gantry Launcher (Studi Kasus: Jembatan Soran Proyek Jalan Tol Solo – Yogyakarta – Nyia Kulon Progo Seksi 1 Paket 1.2) - Suci, R.A.; Wibawa, S.A.; Firdausi, A.A.; Safarizki, H.A. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
The infrastructure growth in Indonesia, particularly on the island of Java, has surged significantly up to the year 2024, one of which includes the Trans-Java toll road project. The aim of this development is to boost the country's economic growth and streamline transportation. A part of the Trans-Java toll road project that is still under construction is the Solo – Yogyakarta – NYIA Kulon Progo Toll Road Project, which connects the cities of Surakarta and Yogyakarta. The construction of the Solo – Yogyakarta – NYIA Kulon Progo Toll Road in Section 1 Package 1.2 is planned to traverse several terrains. For instance, at STA 22 + 767, it will cross the Soran River. Therefore, a bridge needs to be built at STA 22 + 767. The planning of the PCI girder erection method needs to be reviewed, especially for the Soran Bridge, as the initial plan to use the gantry launcher method requires further assessment in terms of time and implementation costs. Hence, an alternative method, the crawler crane, is needed for comparison. From the analysis of time and cost comparisons between the two methods, namely the Crawler Crane method and the Gantry Launcher method for the erection of the PCI girder at the Soran Bridge, the analysis results are as follows: The productivity of equipment using the Crawler Crane method is 0.75 units/hour, and for the Gantry Launcher method, it is 0.19 units/hour, making the productivity faster with the Crawler Crane method. In terms of implementation time based on the analysis, it is 9 days for the Crawler Crane method and 20 days for the Gantry Launcher method, making the implementation 55 percent faster using the Crawler Crane method. Regarding the implementation cost of each method based on the cost analysis, including the procurement and installation of PCI girders, it is IDR 9,219,795,750.00 for the Crawler Crane method and IDR 9,967,224,600.00 for the Gantry Launcher method, making the Crawler Crane method more cost-efficient by 7.49 percent.